Understanding Cultural Taste - Wright, David. author. aut Link
VIII, 188 p.
Keywords: This book will help students and researchers to clarify a complex concept that is often over simplified in media and cultural studies, the sociology of culture and cultural policy. It updates established theoretical and methodological debates in the study of taste and provides an original perspective on a distinct and rich research field.